The Improvement of Kebab Pisang Pusing Business Management in Improving Work Performance and HR Planning - Rini Nurhasanah Sujana; Sarah Adzkia Aulia; Dwi Epty Hidayati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Banana kebab is a type of food made from bananas wrapped in flour batter and fried until crispy. Banana kebabs are generally served with a choice of toppings such as nuts, cheese, sweetened condensed milk, or chocolate. This study aims to analyze and implement steps that are effective in improving the quality of management of the dizzy banana kebab business, with a focus on improving work performance and the planning of human resources (HR). Through qualitative and quantitative research approaches, data was collected from several sources, including direct observation, interviews, and document reviews. The results of the study show that improving HR planning is a key factor in optimizing business management. Manpower needs analysis, recruitment, training, and employee development need to be implemented. In addition, evaluation and improvement of the operational management system is also necessary to improve work performance.